APLIKASI KEAMANAN FILE AUDIO WAV (WAVEFORM) DENGAN TERAPAN ALGORITMA RSA - Raja Nasrul Fuad; Haikal Nando Winata (Universitas Islam Sumatera Utara, 2017)
The WAV file format that is widely used rough on various kinds of multimedia and gaming platforms. Ease of access and technological development with a variety of media to facilitate the exchange of information to various places. The data are important and need to be kept confidential secret for a wide range of security threats so that data can be intercepted and acknowledged by third parties during the shipping process. Of these problems led to the idea to create an application data security functions can secure the data using the RSA algorithm. The programming language is C # with Visual Studio software, the processed data is a sample each byte in WAV file, the header will be the same as that originally WAV files can be played even if the information has been withheld. RSA algorithm can be implemented into a programming language that WAV files can be processed and secured the data.